A methodology to extract the component size distributions in interground composite (limestone) cements. (15th September 2016) - Arora, Aashay; Vance, Kirk; Sant, Gaurav; Neithalath, Narayanan
Highlights: A novel method to extract the particle size distributions of the components in the multi-particle systems. Adopted to interground Portland-limestone cements. Explains the PSD dependence on performance. Abstract: This paper compares the performance of commercial interground Portland-limestone cements (PLC) to those of blended limestone systems. Limestone of four different median sizes is mixed with ordinary portland cement (OPC) to create blends in an attempt to match the particle size distribution of the PLCs. The interground systems are found to outperform the blended systems, plausibly because of the difference in size distributions of the clinker and limestone fractions between the PLCs and the blended systems. A novel methodology to extract the particle size distributions of the components in the interground systems is reported. This method, applicable for several types of multi-component powder systems, considers Rosin-Rammler size distributions for the ground clinker and limestone, and optimizes the parameters of the distribution to obtain a composite distribution of the same fineness as the interground system. The model is verified using a cement hydration and microstructure model.